MENINGKATKAN PENGETAHUAN SANTRI WANITA PONDOK PESANTREN SEBAGAI PENYULUH KESEHATAN/KESEHATAN GIGI - Herawati Djoharnas (Faculty of Dentistry, Universitas Indonesia, 2015)
Maternal and child health problems are still a very big and serious problem in Indonesia, that increase number of death rate, especially during this last years of economic crisis. Posyandu is one health unit developed by the community and with the guidance of the Health Center. It is hope that it could help to overcome the problem. Community health workers are female volunteers in the village to carry out the job in the Posyandu, but lately it is difficult to find volunteers.